Case of Massive Hydatid Pulmonary Embolism Incidentally Discovered in a 56-Year-Old Woman with Posttraumatic Abdominal Pain - Zied Mezgar; Mariem Khrouf; Houda Ben Soltane; Mohamed Mahjoub; Sihem Ben Fredj; Amel Amara; Maher Jedidi; Samar Hajer Sandid; Sarra Zaouali; Ines Waz; Asma Saada; Mehdi Methamem (Case Reports in Pulmonology)
Hydatid pulmonary embolism rarely occurs. It arises from the rupture of a hydatid heart cyst or the opening of a visceral hydatid cyst into the venous circulation. We report a case with pulmonary hydatidosis resulting in a massive bilateral pulmonary embolism in a 56-year-old woman with history of hepatic echinococcosis. A brief overview of clinical features and radiologic findings is presented.